A Tele-detection and referral pAthways model for early childhood cariEs control- a protocol for a randomized factorial study: the TRACE study - Nourhan M. Aly; Mona K. El Kashlan; Nicolas Giraudeau; Maha El Tantawi (BMC, 2024)
Abstract Background Early childhood caries (ECC) is one of the most common childhood diseases affecting the primary teeth of children younger than 6 years of age. ECC progression can be reversed in the early stages although these lesions often go undetected. New approaches are needed to detect oral diseases at an early stage when they can be better controlled. The aim of the study is to assess the effectiveness of ECC tele-detection methods combined with referral pathways with and without user fee removal in controlling ECC. Methods A randomized factorial trial will be used to compare two tele-dentistry detection methods for ECC (intraoral camera and smartphone camera) and two referral pathways (user fee removal versus conventional care). The study will recruit children younger than 6 years of age in marginalized communities in Alexandria, Egypt. The primary outcome is the percentage of teeth receiving indicated care, while the secondary outcomes are the oral health-related quality of life, acceptance of teledentistry by dentists, procedure time, and child cooperation. Two-way analysis of variance will be used to assess the effect of the two factors as between group variables on the outcomes after 6 and 12 months. The interaction between detection methods and referral pathways will also be assessed, and the effect of confounders will be controlled in a multivariable linear regression model. Discussion The findings of this study have the potential to inform clinical practice and oral healthcare policies for ECC management. Successful tele-detection and referral pathways could be integrated into oral healthcare systems, leading to improved oral health outcomes for children. Trial registration The trial has been registered on ClinicalTrials.gov in August 2023 (initial release) ID: NCT06019884.